2015
DOI: 10.1097/nnd.0000000000000158
|View full text |Cite
|
Sign up to set email alerts
|

The Effects of a Prelicensure Extern Program and Nurse Residency Program on New Graduate Outcomes and Retention

Abstract: Organizations are looking to new graduate nurses to fill expected staffing shortages over the next decade. Creative and effective onboarding programs will determine the success or failure of these graduates as they transition from student to professional nurse. This longitudinal quantitative study with repeated measures used the Casey-Fink Graduate Nurse Experience Survey to investigate the effects of offering a prelicensure extern program and postlicensure residency program on new graduate nurses and organiza… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
23
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 29 publications
(23 citation statements)
references
References 14 publications
0
23
0
Order By: Relevance
“…The 9 studies that measured retention found an average 23% increase in retention. Friday et al (2015) was the notable exception, with a 4% decrease in retention at 1 year after the intervention and a 14% decrease at 2 years post intervention.…”
Section: Type Of Componentsmentioning
confidence: 91%
See 1 more Smart Citation
“…The 9 studies that measured retention found an average 23% increase in retention. Friday et al (2015) was the notable exception, with a 4% decrease in retention at 1 year after the intervention and a 14% decrease at 2 years post intervention.…”
Section: Type Of Componentsmentioning
confidence: 91%
“…• Contractual arrangement between the new graduate nurse and the employer • Usually lasts between six months and one year • Delivered in partnership between academia and practice • Involve structured teaching linked to clinical immersion and a mentoring relationship Externships (Friday, et al, 2015) • Opportunities for student nurses to undertake experiential learning in a new clinical area on a short placement…”
Section: Introductionmentioning
confidence: 99%
“…According to nursing literature, the cost of hiring and training a new nurse ranges from $60,000 to $ 96,000 (15) making the retention of the successfully trained nurse a fiscal and operational priority. According to the Texas Center for Nursing Workforce Studies, the Texas median facility turnover is 23.6% for registered nurses (RNs) (16).…”
Section: Overview Of Nurse Residency Programsmentioning
confidence: 99%
“…The education-practice gap associated with newly licensed registered nurses (NLRNs) was first reported in the nursing literature in the 1970s, noting that new graduates were not ready for practice (Kramer, 1974). Educators and health care administrators have escalated efforts to address this issue using a variety of onboarding strategies, although these concerns continue (Friday et al, 2015, Rush et al, 2013. In addition, schools of nursing have deployed strategies to provide better learning opportunities to students to prepare for the realities of practice such as new nurse competencies, job satisfaction, and retention (Rush et al, 2013).…”
mentioning
confidence: 99%